Stigma and Relationship Quality: The Relevance of Racial-Ethnic Worldview in Interracial Relationships in the United States - Brooks, James E.; Morrison, Megan M. (Frontiers in Psychology, 2022)
The current study explored the associations between relationship stigma, Racial-ethnic Worldview (REW; a construct developed as a comprehensive assessment of individual’s perceptions of race and ethnicity), and relationship quality among those in interracial relationships (i.e., participants indicated their race was different than the race of their partner). One type of REW (Color-blind Achieved) was especially susceptible to the negative consequences of stigma from family members. Other significant differences in relationship quality and relationship stigma were found based on REW. Most notable is that individuals who acknowledge institutional racism, have positive intergroup attitudes, and a positive ethnic identity reported better relationship quality than those who denied institutional racism and/or had less positive attitudes toward their own ethnic group. These results demonstrate the utility of REW in contextualizing experiences of individuals in interracial relationship as it relates to perceived stigma and relationship quality. The study offers a critical account of how individuals understanding of the racial and ethnic social context shapes relationship outcomes for those in interracial relationships in the United States.